Analysis of Thin-Walled Bars With Open and Closed-Open Cross-Sections - Garstecki, A.; Kąkol, W.; Rzeszut, K. (Engineering Transactions, 2000)
The paper presents the numerical analysis of global and local buckling of columns made of steel cold-rolled, very thin-walled cross-sections of sigma (E) and double sigma (2E) type. Variation of the buckling stress for a wide range of slenderness ratio is presented. The deformation of the contour associated with different buckling modes and warping of open and closed-open sections is discussed, too. The exactness and numerical efficiency of different methods are studied on several examples. Finite Element Method incorporating the Vlasov beam element and shell element is compared with the Finite Strip Method.